2017
DOI: 10.4174/astr.2017.92.4.214
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between preoperative volumetry and real graft weight: comparison of two volumetry programs

Abstract: PurposeLiver volumetry is a vital component in living donor liver transplantation to determine an adequate graft volume that meets the metabolic demands of the recipient and at the same time ensures donor safety. Most institutions use preoperative contrast-enhanced CT image-based software programs to estimate graft volume. The objective of this study was to evaluate the accuracy of 2 liver volumetry programs (Rapidia vs. Dr. Liver) in preoperative right liver graft estimation compared with real graft weight.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The ratio of the calculated volume and the weight of the graft should be at least 0.8% in order to protect the recipient from small-for-size phenomena (cellular damage, liver with decreased capacity for metabolism, synthesis, ascites), and the ratio should be <3% to avoid large-for-size phenomena (poor liver perfusion, increased abdominal pressure). The volume of the remaining liver should be at least 30% to protect the donor from life-threatening consequences [ 1 ].…”
mentioning
confidence: 99%
“…The ratio of the calculated volume and the weight of the graft should be at least 0.8% in order to protect the recipient from small-for-size phenomena (cellular damage, liver with decreased capacity for metabolism, synthesis, ascites), and the ratio should be <3% to avoid large-for-size phenomena (poor liver perfusion, increased abdominal pressure). The volume of the remaining liver should be at least 30% to protect the donor from life-threatening consequences [ 1 ].…”
mentioning
confidence: 99%
“…It is widely accepted that studies using intraoperative liver volumetric measurements are based on the assumption that the density value is on the order of 1 g/mL, to facilitate the conversion of volumetric values to weight values. 20…”
Section: Volumetric Analysismentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to have evaluated the performance of liver volumetry involving numerous software programs and clinicians (multicentic evaluation) because most previously published studies only compared two or three software used by a few operators [8,9,11,15,22,23,30]. Our work therefore reflects the practices actually applied in French HPB centres.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…In terms of liver volumetric calculations, some authors have also reported clinically significant inter-and intra-observer variability, but the reliability of this tool remains widely accepted because of the statistically strong correlation between estimates and intraoperative measurements in most series [22,23]. Given this apparent contradiction (statistical vs clinical significance), our goal was to evaluate the reliability of volumetric assessment in the settings of deceased-donor liver transplantation (DDLT) (cirrhotic livers) and LDLT (healthy livers), aiming to determine the true difference between volumetric estimations and intraoperative measurements.…”
Section: Introductionmentioning
confidence: 99%